Endogenous retrovirus expression activates type-I interferon signaling in an experimental mouse model of mesothelioma development. (1st June 2021) - Sun, Suna; Frontini, Francesca; Qi, Weihong; Hariharan, Ananya; Ronner, Manuel; Wipplinger, Martin; Blanquart, Christophe; Rehrauer, Hubert; Fonteneau, Jean-François; Felley-Bosco, Emanuela
Abstract: Early events in an experimental model of mesothelioma development include increased levels of editing in double-stranded RNA (dsRNA). We hypothesised that expression of endogenous retroviruses (ERV) contributes to dsRNA formation and type-I interferon signaling. ERV and interferon stimulated genes (ISGs) expression were significantly higher in tumor compared to non-tumor samples. 12 tumor specific ERV ("MesoERV1-12") were identified and verified by qPCR in mouse tissues. "MesoERV1-12" expression was lower in mouse embryonic fibroblasts (MEF) compared to mesothelioma cells. "MesoERV1-12" levels were significantly increased by demethylating agent 5-Aza-2′-deoxycytidine treatment and were accompanied by increased levels of dsRNA and ISGs. Basal ISGs expression was higher in mesothelioma cells compared to MEF and was significantly decreased by JAK inhibitor Ruxolitinib, by blocking Ifnar1 and by silencing Mavs. "MesoERV7" promoter was demethylated in asbestos-exposed compared to sham mice tissue as well as in mesothelioma cells and MEF upon 5-Aza-CdR treatment. These observations uncover novel aspects of asbestos-induced mesothelioma whereby ERV expression increases due to promoter demethylation and is paralleled by increased levels of dsRNA and activation of type-I IFN signaling. These features are important for early diagnosis and therapy. Highlights: Endogenous retrovirus (ERV) expression and RNA editing activity increase upon mesothelioma development. Increased tumor specific "Meso ERV" expression is due to promoter demethylation. Upregulation of dsRNA and activation of type-I interferon pathways are associated with "MesoERV" expression. The observations are important for mesothelioma early diagnosis and therapy.